An experimental study of the agreement of self-administration and telephone administration of the Timeline Followback interview. - Maisto, Stephen A; Conigliaro, Joseph C; Gordon, Adam J; McGinnis, Kathleen A; Justice, Amy C (Journal of studies on alcohol and drugs, 2008)
The Timeline Followback (TLFB) interview has become state-of-the-science for the collection of retrospective self-reports of daily alcohol consumption. Such data are especially useful for addressing questions of the co-occurrence of quantity of alcohol consumption and other behaviors, such as HIV-related risky sex, on the event level. The purpose of this study was to determine if the TLFB could be used effectively by self-administration compared with the more costly telephone interview in a large, multisite observational study of HIV-positive and HIV-negative adults.
Keywords: Adult; Alcohol Drinking; Alcoholism; Female; Health Behavior; HIV Seropositivity; Humans; Interviews as Topic; Male; Medical Records; Middle Aged; Psychometrics; Questionnaires; Reproducibility of Results; Retrospective Studies; Self Disclosure; United States; Unsafe Sex; Veterans